The Effect of Socioeconomic Status on Delinquency Across Urban and Rural Contexts: Using a Genetically Informed Design to Identify Environmental Risk. (September 2017) - Connolly, Eric J.; Lewis, Richard H.; Boisvert, Danielle L.
An extensive line of research has demonstrated that low socioeconomic status (SES) is a risk factor for adolescent delinquent behavior. The possibility that low SES affects adolescent's risk for engaging in delinquent behavior has garnered a significant amount of empirical and public attention, given its implications for delinquency prevention. However, few studies have examined the association between low SES and delinquent behavior across urban and rural contexts in the United States. Moreover, much is unknown about the strength of the association between low SES and delinquency across urban and rural context after controlling for common genetic liabilities that often cluster within different levels of SES. The present study aimed to address these existing gaps in the literature by conducting a genetically informed analysis of sibling pairs from a nationally representative sample of U.S. youth. The results revealed that shared environmental factors accounted for 17% of the population variation in adolescent delinquent behavior among adolescents growing up in urban contexts, and 3% of this family-wide environmental effect was accounted for by SES. No evidence of a family-wide environmental effect on population variation in delinquent behavior was found among adolescents from rural contexts. Findings from the present study suggest that the association between low SES and delinquency in urban contexts in the United States may be a true environmental effect and highlight the utility of using genetically informed research designs to better understand the extent to which social contexts influence adolescent delinquent behavior.